RETROSPEKSI REFORMASI DESA - Anita Marianata; Yorry Hardayani (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2019)
Changes in village governance are also known as village governance reforms. The journey of bureucratic reform has a significant impact on the administration of government. Government institutions have carried out bureaucratic reform on an ongoing basis. Bureaucratic reform is related to better changes to government systems and management, services and the increase in birokrat resources so that these changes have good implications for aspects of governance. The purpose of the research to be carried out namely: know about changes in the village government bureaucracy, know and describe village changes with the BUMD. The research method used is desriptive qualitative research, with observation data collection techniques, FGD, in-depth interviews and documentation, to obtain an objective picture of a study. Changes in village governance are reflected in the birth of BUM Desa as a result of granting authority to the village government, especially Desa Durian Demang. Based on the results of the interview, it can be seen that the changes that occured in Durian Demang, occurred physically and also non-physically. Physical changes such as the construction of village facilities, namely the village office in 2019, have been completed based on the village budget in 2018, in addition, village roads begun to be repaired. For physical development also occurred significantly, where in Durian Demang a general hospital in Bengkulu Tengah district was also built. For non-physical development, Durian Demang community has also begun to innovate in managing BUM Desa by processing agricultural products. Also in 2019, Durian Demang changed the name of the tourist destination to Dewi Dumang